Geometrical dimensioning and tolerancing for design, manufacturing and inspection : a handbook for geometrical product specification using ISO and ASME standards - Henzold, G.
Geometrical tolerancing is used to specify and control the form, location and orientation of the features of components and manufactured parts. This book presents the state of the art of geometrical tolerancing, covers the latest ISO and ANSI/ASME standards and is a comprehensive reference and guide for all professional engineers, designers, CAD users, quality managers and anyone involved in the creation or interpretation of CAD plans or engineering designs and specifications. *For all design and manufacturing engineers working with these internationally r.